Capturing functional two-dimensional nanosheets from sandwich-structure vermiculite for cancer theranostics - Xiaoyuan Ji (Nature Portfolio, 2021)
Clay-based nanomaterials are of wide interest but problems extracting the 2D functional core layers have limited potential applications. Here, the authors report on the wet exfoliation of vermiculite by alkali etching to obtain the core layers and explore the application of the materials in cancer theranostics.